The effect of perioperative blood transfusion on kidney functions in total knee Arthroplasty - Sen, Baran (Pak J Med Sci, 2019)
OBJECTIVE: Various studies have examined the effects of perioperative blood transfusion on kidney functions. In this study, we investigated the effects of blood transfusion on the kidney functions of patients undergoing total knee arthroplasty. METHODS: : This retrospective study was carried out on 216 patients who had undergone total knee arthroplasty between January 2016 and January 2017. The patients were divided into two groups according to the level of blood transfusion used during surgery. Group-1 comprised 157 patients (72.7%) needing a blood transfusion of less than three units, while the 59 (27.3) patients in Group-2 required three or more than three units. RESULTS: No statistical difference was found between the two groups regarding hypertension before surgery, diabetes mellitus, chronic kidney failure, smoking habits or lung disease (p> 0.05). Likewise, there was no significant difference related to pulmonary and other complications or mortality (p> 0.05). When the groups were compared according to their blood parameters, no statistical differences in postoperative renal or other system functions were found (p> 0.05). CONCLUSIONS: Blood transfusion does not have a negative effect on postoperative blood urea nitrogen (BUN) and creatinine levels, or glomerular filtration rate in total knee arthroplasty.